Employment and Poverty under Neoliberal Capitalism - Patnaik, Prabhat (Social research, 2024)
Neoliberal capitalism, characterized by freer movement of goods and services and capital, including finance, across country borders, keeps down real wages everywhere even as labor productivity increases. This raises income inequalities, creating an ex ante tendency toward overproduction, which underlies the current stagnation and growing unemployment in the world economy. This crisis cannot be overcome within neoliberalism, since globalized finance opposes larger state expenditure financed through heavier taxation of the rich or a larger fiscal deficit. This underlies the current pervasive tendency toward neofascism. Overcoming neofascism requires transcending neoliberalism by mobilizing working people around a rights-based welfare state.